Scholarships or Student Loans? Subsidizing Higher Education in the Presence of Moral Hazard - Alessandro Cigno; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2003)
Student loans, even income-contingent ones, are not optimal. Potential university students with the appropriate characteristics should be offered a scholarship, dependent on both need and merit. The award of the scholarship should be conditional on the choice of university degree, but students with a natural aptitude for studies that do not hold the prospect of a well paid job should not be pushed towards potentially more lucrative ones. The scheme should be financed by a graduate tax that re-distributes from the better paid to the academically more successful.
Keywords: D82; I28; 330; scholarships; student loans; graduate tax; principal-agent; moral hazard